Language in Literature - Jakobson, Roman 1896-1982; Pomorska, Krystyna 1928-1986; Rudy, Stephen (Cambridge, MA London Belknap Press of Harvard University Press, 1987)
Roman Jakobson was one of the great minds of the modern world," Edward J. Brown has written, "and the effects of his genius have been felt in many fields: linguistics, semiotics, art, structural anthropology, and, of course, literature." At every stage in his odyssey from Moscow to Prague to Denmark and then to the United States, he formed collaborative efforts that changed the very nature of each discipline he touched. This book is the first comprehensive presentation in English of Jakobson's major essays on the intertwining of language and literature: here the reader will learn how it was that Jakobson became legendary.Jakobson reveals himself as one of the great explorers of literary art in our day--a critic who revealed the avant-garde thrust of even the most worked-over poets, such as Shakespeare and Pushkin, and enabled the reader to see them as the innovators they were. Jakobson takes the reader from literature to grammar and then back again, letting points of structural detail throw a sharp light on the underlying form and linking thereby the most disparate realms into a coherent whole. In his essays we can also learn to appreciate his search for a fully systematic, nonmetaphysical understanding of the workings of literature: Jakobson made possible a deep structural analysis that did not exist before.Among the essential items in this collection are such classics as "Linguistics and Poetics" and "On a Generation That Squandered Its Poets" and illuminations of Baudelaire, Yeats, Turgenev, Pasternak, and Blake, as well as the famous pieces on Shakespeare and Pushkin. The essays include fundamental theoretical statements, structural analyses of individual poems, explorations of the connections between poetry and experience, and semiotic perspectives on the structure of verbal and nonverbal art. This will become a basic book for contemplating the function of language in literature--a project that will continue to engross the keenest readers.
Traces of water damage and (old) mould
Keywords: Literature; Semiotics; Hermeneutics